PELATIHAN PEMBUATAN BROWNIES DARI TEPUNG TONGKOL JAGUNG DI DESA TAMANSARI - Wardhani, Salza Belila Kusuma; Wardhani, Shindhy Nurulita Kusuma; Cahyani, Santi Berliana (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
Food is a basic need that humans need and must fulfill at all times. Achieving food security can be started by optimizing the potential of local food in each region. A corn is a product of the land that has a variety of benefits, ranging from stems, skins, seeds, and leaves, to corn cobs. However, not many people know how to utilize corn cobs. Corn cob waste contains cellulose, lignin, and hemicellulose. This is the author's concern about processing corn cobs that were originally discarded into food that has selling value. This training can provide knowledge to the community in processing the right agricultural waste. The training activities involved two sequences, including planning and demonstration stages. The demonstration was the making of brownies from corncob flour. Brownies are cakes processed through a steaming or baking process that have a square, rectangular, or circular shape. The outcome of this activity is that local people know that corn cobs can be processed into flour and other products such as brownies.